Substantivity of Carbodiimide Inhibition on Dentinal Enzyme Activity over Time. (July 2017) - Mazzoni, A.; Angeloni, V.; Sartori, N.; Duarte, S.; Maravic, T.; Tjäderhane, L.; Pashley, D.H.; Tay, F.R.; Breschi, L.
The use of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide HCl (EDC) has recently been investigated for its effectiveness in the prevention of collagen degradation over time and the improvement of resin-dentin bond durability. The objective of the present study was to evaluate the effects of a 0.3 M EDC-containing conditioner on endogenous enzymatic activities within the hybrid layer (HL) created by a self-etch or an etch-and-rinse adhesive after 1 y. The activity within the HL was examined using in situ zymography and confocal laser scanning microscopy after 24 h or 1-y storage in artificial saliva. Dentin specimens were bonded with Clearfil SE Bond (CSE) or XP Bond (XPB). For CSE, the self-etching primer was applied and treated with 0.3 M EDC for 1 min, and then the bonding agent was applied. For XPB, dentin was etched and treated with 0.3 M EDC for 1 min and then bonded with the primer-bonding agent. Control specimens were prepared without EDC treatment. Slices containing the adhesive-dentin interface were covered with fluorescein-conjugated gelatin and observed with a multiphoton confocal microscope. Fluorescence intensity emitted by hydrolyzed fluorescein-conjugated gelatin was quantified, and the amount of gelatinolytic activity was represented by the percentage of green fluorescence emitted within the HL. After 24 h of storage, enzymatic activity was detected by in situ zymography within the HLs of both tested adhesives, with XPB higher than CSE ( P < 0.05). Almost no fluorescence signal was detected when specimens were pretreated with EDC compared to controls ( P < 0.05). After 1 y of storage, enzymatic activities significantly increased for all groups (excluding XPB control) compared to 24-h storage ( P < 0.05), with EDC pretreated specimens exhibiting significantly lower activity than controls ( P < 0.05). The present study showed, for the first time, that the use of EDC for both the self-etch and the etch-and-rinse approaches results in the reduction but not complete inhibition of matrix-bound collagenolytic enzyme activities over time in the HL.